The lubricating effect of iPS-reprogrammed fibroblasts on collagen-GAG scaffolds for cartilage repair applications. (February 2021) - Santarella, Francesco; Simpson, Christopher R.; Lemoine, Mark; McGrath, Sean; Cavanagh, Brenton; Smith, Avi; Murphy, Ciara M.; Garlick, Jonathan A.; O'Brien, Fergal J.; Kearney, Cathal J.
Abstract: Tissue engineering products, like collagen-glycosaminoglycan scaffolds, have been successfully applied to chondrogenic defects. Inducible Pluripotent Stem cell (iPS) technology allows reprograming of somatic cells into an embryonic-like state, allowing for redifferentiation. We postulated that a fibroblast cell line (BJ cells – 'pre-iPSF') cycled through iPS reprogramming and redifferentiated into fibroblasts (post-iPSF) could lubricate collagen-glycosaminoglycan scaffolds; fibroblasts are known to produce lubricating molecules (e.g., lubricin) in the synovium. Herein, we quantified the coefficient of friction (CoF) of collagen-glycosaminoglycan scaffolds seeded with post-iPSF; tested whether cell-free scaffolds made of post-iPSF derived extracellular matrix had reduced friction vs. pre-iPSF; and assessed lubricin quantity as a possible protein responsible for lubrication. Post-iPSF seeded CG had 6- to 10-fold lower CoF versus pre-iPSF. Scaffolds consisting of a collagen and pre-/post-iPSF extracellular matrix blend outperformed these cell-seeded scaffolds ( 5-fold lower CoF), yielding excellent CoF values close to synovial fluid. Staining revealed an increased presence of lubricin within post-iPSF scaffolds (confirmed by western blotting) and on the surface of iPSF-seeded collagen-glycosaminoglycan scaffolds. Interestingly, when primary cells from patient biopsy-derived fibroblasts were used, iPS reprogramming did not further reduce the already low CoF of these cells and no lubricin expression was found. We conclude that iPS reprogramming activates lubricating properties in iPS-derived cells in a source cell-specific manner. Additionally, lubricin appears to play a lubricating role, yet other proteins also contribute to lubrication. This work constitutes an important step for understanding post-iPSF lubrication of scaffolds and its potential for cartilage tissue engineering. Graphical abstract: Image 1 Highlights: Post-iPSF results in lower friction when seeded on CG scaffolds. Scaffolds fabricated using post-iPSF ECM matches synovial fluid lubrication. Lubricin was identified as a possible protein responsible for the lubrication. Lubricating properties are not activated in all iPS derived cells. Lubricating scaffolds for joint repair is a promising, yet understudied approach.